2013
DOI: 10.1016/j.jarmac.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining guilty knowledge in human intelligence interrogations: Comparing accusatorial and information-gathering approaches with a novel experimental paradigm.

Abstract: Substantial research has assessed interrogations seeking to obtain a criminal confession, and consequently much has been learned regarding the potential problems with confession evidence. However, an increasing focus on counter-terrorism, and therefore intelligence interrogations, reveals an obvious gap in the literature. Intelligence interrogations are primarily focused on collecting information from individuals as opposed to a confession linked to an alleged event, and little of the extant psychological lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 18 publications
(30 reference statements)
3
60
0
Order By: Relevance
“…We also note that because a dichotomous, yes/no confession variable (as opposed to amount of information) has been the most-often used outcome in the studies we reviewed (and ultimately deemed eligible), our focal outcome measure by necessity is also confession (true and false). A novel experimental paradigm focusing on the elicitation of guilty knowledge from noncooperative individuals has only recently been introduced to the empirical literature (see Evans et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…We also note that because a dichotomous, yes/no confession variable (as opposed to amount of information) has been the most-often used outcome in the studies we reviewed (and ultimately deemed eligible), our focal outcome measure by necessity is also confession (true and false). A novel experimental paradigm focusing on the elicitation of guilty knowledge from noncooperative individuals has only recently been introduced to the empirical literature (see Evans et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Gathering information from human sources is a fundamental and unceasing endeavour in the prevention of crime. However, researchers have only recently begun to develop and evaluate methods for gathering human intelligence (Evans et al ., ; Granhag, Cancinos Montecinos, & Oleszkiewicz, ; Granhag, Vrij, & Meissner, ; Justice, Bhatt, Brandon, & Kleinman, ). Broadly speaking, the aim of this work is to be able to suggest effective and ethically defensible strategies for collecting information from human sources.…”
Section: Introductionmentioning
confidence: 99%
“…Different experimental paradigms in social psychology using students or volunteers have shown that an information-gathering approach yields more relevant information than an accusatorial approach and leads to more diagnostic impressions by third party observers (see for instance Evans et al, 2013). Positive (praise) and negative (deprecation) emotional approaches to interrogation are more efficient than a direct, accusatorial approach (Evans et al, 2014).…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%